PENGARUH MODEL PEMBELAJARAN PREDICT, OBSERVE, EXPLAIN, WRITE (POEW) TERHADAP PEMAHAMAN KONSEP FISIKA DITINJAU DARI JENIS KELAMIN KELAS XI IPA SMA NEGERI 1 EMPANG - Anita Fitriani; Saiful Prayogi; Samsun Hidayat (Universitas Pendidikan Mandalika, 2015)
This study was aimed to know 1) the effect of Predict, Observe, Explain, Write (POEW) learning model toward physics conceptual understanding, 2) the effect of gender toward physics conceptual understanding, and 3) the effect of POEW learning model and gender toward physics conceptual understanding. The kind of This study was experimental research with postest only control grup design. Sample of this study were both science class 11st IPA1 and 11st IPA2 which choosen by randomizing from 3 grup of science class 11st of SMAN 1 Empang. The design of this study using factorial 2x2. The instrument of this study was essay test which have been valid and reliable to ghater information about how the physics conceptual understanding of student. Then the data of physics conceptual understanding was analysed by analysis of variance (ANOVA) using SPSS. Thus from the reshult of data we got some information were 1) the effect of POEW learning model toward physics conceptual understanding have 0,000 significance value which lower than α was 0,05. 2) the effect of gender toward physics conceptual understanding have 0,000 significance value which lower than α was 0,05. 3) the effect of interaction both POEW learning model and gender toward physics conceptual understanding have 0,002 significance value which lower than α was 0,05. It was means that POEW was affecting physics conceptual understanding based on gender at at 11st science students of SMAN 1 Empang.